(untitled) (Constructionism Conference Proceedings, 2025)
This study investigates the integration of artificial intelligence (AI) into constructionist learning environments to enhance creativity, inclusion, and personalized STEM education, especially for neurodiverse learners. Grounded in Seymour Papert’s theory of Constructionism, it explores how AI tools – like virtual reality, social robots, and intelligent tutors – can support hands-on, learner-centered experiences. A narrative literature review of over 30 studies reveals that AI can personalize content, foster engagement, and support social interaction. However, challenges include access disparities, ethical concerns, and limited teacher training. The findings highlight AI’s transformative potential when combined with constructionist pedagogy to create more inclusive and equitable education systems.